A Comparison of Pollen and Syrup Exposure Routes in Bombus impatiens (Hymenoptera: Apidae) Microcolonies: Implications for Pesticide Risk Assessment. Issue 3 (5th May 2022) - Weitekamp, Chelsea A; Koethe, Robert W; Lehmann, David M
Abstract: Bumble bees are important pollinators for both native plants and managed agricultural systems. Accumulating evidence has shown that pesticides, including neonicotinoids, can have a range of adverse effects on bumble bee health. Most laboratory studies that assess the effects of chronic neonicotinoid exposure on bumble bees use syrup as the delivery vehicle, rather than pollen. However, in the field, it is likely that bumble bees are exposed to neonicotinoids in both nectar (syrup) and pollen. To examine the potential for different effects based on the vehicle, we compared two studies of chronic exposure to the neonicotinoid acetamiprid in Bombus impatiens microcolonies. We examined correlations between microcolony endpoints and identified associations between the timing of colony pollen and syrup consumption and drone production. Furthermore, in line with previous results, we found that average drone weight was affected at a range of doses only when microcolonies were exposed to acetamiprid via pollen. In general, our analyses point to the importance of the treatment vehicle and suggest that critical effects on developing brood could be missed when neonicotinoid exposure occurs only through syrup.